The rs13075270 and rs13092160 polymorphisms of CCR1 and CCR3 genes on oral aphthous-like lesions in PFAPA syndrome - Li, Weiwei; Li, Na; Yang, Guohai; Li, Yanhua (Cellular and Molecular Biology, 2022)
Fever is a common symptom of infection in children. Periodic fever syndromes are less common but more complex. One of these Periodic fever syndromes is PFAPA (periodic fever, aphthous stomatitis, pharyngitis, cervical adenitis) syndrome which is known as the most benign syndromes. The cause of this disease is unknown. Various factors, including environmental and genetic factors, are involved in the development of this disease. In this study, the association of rs13075270 and rs13092160 polymorphisms were investigated in CCR1 and CCR3 genes with susceptibility to this syndrome in the Chinese population. In this regard, 38 patients with PFAPA syndrome and 100 healthy individuals were selected. After DNA sampling and extraction, polymorphisms of CCR1 and CCR3 receptor genes were examined by the PCR-RFLP method. Findings were analyzed using SPSS software version 22 with a significant level of P <0.05. The frequency of T/T genotype rs13092160 polymorphism in the patient and control groups was 78.95% and 83%, respectively, C/T genotype was 21.05% and 17% (P = 0.421). The frequency of the C/C genotype was 0 in both groups. Regarding rs13075270 polymorphism, the frequency of T/T genotype in patient and control groups was 15.79% and 81%, C/T genotype was 78.95% and 18% and C/C genotype was 5.26% and 1%, respectively (P<0.05). Thus, in rs13075270 polymorphism, the C/T genotype was associated with the risk of PFAPA syndrome (P<0.05), but rs13092160 polymorphism did not show a significant difference between individuals with PFAPA syndrome and controls.